1995
DOI: 10.1074/jbc.270.39.22816
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nucleobase Transport in Rabbit Choroid Plexus

Abstract: The overall goal of this study was to determine the mechanisms by which nucleobases are transported in the choroid plexus. Choroid plexus tissue slices were obtained from the lateral ventricles of rabbit brains and depleted of ATP with 2,4-dinitrophenol. In the presence of an initial inwardly directed Na ؉ gradient, hypoxanthine accumulated in the tissue slices against a concentration gradient. Na ؉ -stimulated hypoxanthine uptake was saturable with a K m of 31.1 ؎ 9.71 M and a V max of 2.69 ؎ 0.941 nmol/g/s (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Of particular note is that the affinity of both purine and pyrimidine bases for this co-transporter is high (apparent K m values in the range 1-10 µM) and that adenine is not a permeant. Recently, a Na + -dependent nucleobase transporter in rabbit choroid plexus has been described with properties distinct from those nucleobase co-transporters in kidney and heart [22].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note is that the affinity of both purine and pyrimidine bases for this co-transporter is high (apparent K m values in the range 1-10 µM) and that adenine is not a permeant. Recently, a Na + -dependent nucleobase transporter in rabbit choroid plexus has been described with properties distinct from those nucleobase co-transporters in kidney and heart [22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CNT1, which transports pyrimidine nucleosides more preferentially than purine nucleosides, is highly expressed in the epithelial tissues such as small intestine, kidney, and liver (8 -11). It is also known that CNT1 is localized at the apical membrane of intestinal epithelial cells, suggesting its physiological and pharmacological roles in the absorption of nucleosides and their analogs in the small intestine.However, transporters specific for nucleobases have not been identified in mammals, although their presence has long been postulated (3,4,(12)(13)(14)(15)(16)(17). Our earlier study using the everted sacs of the rat small intestine demonstrated that the uptake transport of 5-fluorouracil (5-FU), 2 a uracil analog used for cancer chemotherapy, occurs in a saturable and sodium-dependent * This work was supported in part by a grant-in-aid for young scientists (B) from the Ministry of Education, Culture, Sports, Science and Technology, Japan, and a grant-in-aid for research in Nagoya City University.…”
mentioning
confidence: 99%
“…However, transporters specific for nucleobases have not been identified in mammals, although their presence has long been postulated (3,4,(12)(13)(14)(15)(16)(17). Our earlier study using the everted sacs of the rat small intestine demonstrated that the uptake transport of 5-fluorouracil (5-FU), 2 a uracil analog used for cancer chemotherapy, occurs in a saturable and sodium-dependent * This work was supported in part by a grant-in-aid for young scientists (B) from the Ministry of Education, Culture, Sports, Science and Technology, Japan, and a grant-in-aid for research in Nagoya City University.…”
mentioning
confidence: 99%
“…16,17) Equilibrative nucleobase transport has been observed in human erythrocytes, human T-lymphoblastoid cells, LLC-PK1 cells, rabbit cornea cells and S49 mouse-derived lymphoma cells, [18][19][20][21] whereas concentrative nucleobase transport occurs in kidney, intestine, placenta, and choroid plexus. 19,[22][23][24][25][26] However, little is yet known about the molecular basis of nucleobase transport in mammalian cells.…”
mentioning
confidence: 99%